Gut microbiome markers in subgroups of HLA class II genotyped infants signal future celiac disease in the general population: ABIS study - Milletich, Patricia L.; Ahrens, Angelica P.; Russell, Jordan T.; Petrone, Joseph R.; Berryman, Meghan A.; Agardh, Daniel; Ludvigsson, Jonas F.; Triplett, Eric W.; Ludvigsson, Johnny (Frontiers in Cellular and Infection Microbiology, 2022)
Although gut microbiome dysbiosis has been illustrated in celiac disease (CD), there are disagreements about what constitutes these microbial signatures and the timeline by which they precede diagnosis is largely unknown. The study of high-genetic-risk patients or those already with CD limits our knowledge of dysbiosis that may occur early in life in a generalized population. To explore early gut microbial imbalances correlated with future celiac disease (fCD), we analyzed the stool of 1478 infants aged one year, 26 of whom later acquired CD, with a mean age of diagnosis of 10.96 ± 5.6 years. With a novel iterative control-matching algorithm using the prospective general population cohort, All Babies In Southeast Sweden, we found nine core microbes with prevalence differences and seven differentially abundant bacteria between fCD infants and controls. The differences were validated using 100 separate, iterative permutations of matched controls, which suggests the bacterial signatures are significant in fCD even when accounting for the inherent variability in a general population. This work is the first to our knowledge to demonstrate that gut microbial differences in prevalence and abundance exist in infants aged one year up to 19 years before a diagnosis of CD in a general population.